Логічний аналіз та оброблення даних задля класифікації зображень на підставі формування статистичного центру опису - Гороховатський, В. О.; Гадецька, С. В.; Пономаренко, Р. П. (My University, 2019)
LOGICAL ANALYSIS AND PROCESSING OF DATA FOR THE CLASSIFICATION OF IMAGES ON THE BASIS OF FORMATION OF STATISTICAL CENTER DESCRIPTION The subjects of research are the models for classifying images in the description space as multiple key point descriptors when recognizing visual objects in computer vision systems. The goal is to develop a structural method of classification by introducing logical data processing using probability distribution in the form of statistical center. The tasks include the development of mathematical and software models to calculate the relevance of image descriptions using logical analysis, study of properties, variations of application, values of model parameters, evaluation of the results of processing the experimental image database. The methods are used: a BRISK detector for forming the key point descriptors, data mining, mathematical statistics, means of determining relevance for data sets, software modeling. The following results were obtained. The effectiveness of a method of classification based on logical analysis using statistical centers that depend on the distances between centers of etalons. Logical analysis simplifies processing and increases classification speed. The best results on the classification of individual descriptors were shown by the use of refined centers. Using a concentrated portion of the description data allows you to focus more closely on its differences with other descriptions. Conclusions. The contribution of the paper is the improvement of the image classification based on the implementation of logical analysis of the statistical center description, which allows modifying the composition of the description while maintaining the properties of objects in terms of effective classification. The practical significance of the paper is the achievement of the accepted relevance level according to a defined model of relevance, to validate the proposed modifications to the processing of sample images, to develop software models for implementing the described methods of classification in computer vision. Keywords: structural image recognition methods, key point, BRISK detector, descriptor, statistical center, concentrated description, logical analysis, relevance of descriptions, the effectiveness of classification, aggregated image.
Keywords: структурні методи класифікації зображень; ключова точка; детектор BRISK; статистичний центр; концентрований опис; релевантність описів